Differential diagnosis of melasma and hyperpigmentation. Issue 1 (3rd August 2022) - Honigman, Anthony; Rodrigues, Michelle
Abstract: Background : Melasma is a common disorder of acquired hyperpigmentation affecting millions of people worldwide, predominantly women. Despite the incidence, there are numerous hyperpigmentary conditions which may clinically resemble melasma. The differential diagnosis of melasma is therefore wide and may prove to be a diagnostic challenge for clinicians. This can delay the appropriate treatment, adversely impacting sufferers. Our review aims to provide clinicians with an understanding of and a comprehensive approach to assessing, diagnosing and treating melasma and other disorders of hyperpigmentation.